Legal basis of control in the field of environmental protection during radiation contamination. (Journal of actual problems of jurisprudence, 2016)
In this article the author examines the main provisions of environmental control. Examines the legal framework for the control in the field of environmental protection during radiation contamination. Need for state regulation in the field of environmental protection and natural resources associated with the growing problem of environmental safety.
Keywords: environmental monitoring; state environmental control; public environmental control